2011
DOI: 10.7439/ijbar.v2i1.22
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Remedies for Diabetes: An Overview

Abstract: Today’s fast and furious life style one of the major factors, which precipitate the diabetes mellitus. The treatment of diabetes mellitus, which includes the use of insulin and oral hypoglycemic agents sulfonylurea, biguanides. Diabetes mellitus one of the major disorder which is growing at faster rate second after cancer. Long-term use of these medications will create unwanted side effects, resulting uncontrolled increase in blood sugar as well as complications with heart diseases also diabetics are highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 2 publications
0
8
0
3
Order By: Relevance
“…11 Günümüzde dünya nüfusunun %2,8'inde gö-rülen bu hastalığın görülme oranının 2025 itibarıyla %5,4'e yükseleceği öngörülmektedir. 7 Diyabetin patolojik karakteri vücuttaki hücre-lerde glukoz kullanımının azalmasına, yağ depo alanlarından yağların taşınmasının artması sonucu anormal yağ metabolizmasının oluşmasına ve dokularda protein boşalmasına bağlıdır. 7 Pankreasın Langerhans adacıklarında yer alan iki hücreden alfa hücreleri glukagon hormonunun, beta hücreleri ise insülin hormonunun sentezinde görevlidir.…”
Section: Di̇abetes Melli̇tusunclassified
See 2 more Smart Citations
“…11 Günümüzde dünya nüfusunun %2,8'inde gö-rülen bu hastalığın görülme oranının 2025 itibarıyla %5,4'e yükseleceği öngörülmektedir. 7 Diyabetin patolojik karakteri vücuttaki hücre-lerde glukoz kullanımının azalmasına, yağ depo alanlarından yağların taşınmasının artması sonucu anormal yağ metabolizmasının oluşmasına ve dokularda protein boşalmasına bağlıdır. 7 Pankreasın Langerhans adacıklarında yer alan iki hücreden alfa hücreleri glukagon hormonunun, beta hücreleri ise insülin hormonunun sentezinde görevlidir.…”
Section: Di̇abetes Melli̇tusunclassified
“…7 Diyabetin patolojik karakteri vücuttaki hücre-lerde glukoz kullanımının azalmasına, yağ depo alanlarından yağların taşınmasının artması sonucu anormal yağ metabolizmasının oluşmasına ve dokularda protein boşalmasına bağlıdır. 7 Pankreasın Langerhans adacıklarında yer alan iki hücreden alfa hücreleri glukagon hormonunun, beta hücreleri ise insülin hormonunun sentezinde görevlidir. Her iki hormon da glukoz metabolizmasının düzenlenmesinde rol almakta ve kandaki glukoz düzeylerini belli düzeyde tutmaktadır.…”
Section: Di̇abetes Melli̇tusunclassified
See 1 more Smart Citation
“…1 Around 3% of the world's population has diabetes and it is concluded that it may exceed 5.4% by the year 2025. 2 In Turkey, 7.4% of the population has diabetes, and it is also estimated that the number of patients will increase to 9.6% of the population by 2030. 3 Studies on diabetes therapy have gained interest due to its unwanted effects on human life e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a higher incidence of the risk factors, the prevalence of diabetes is increasing worldwide, especially in developing countries 2 . 2.8% of world population suffer from diabetes and it is concluded that it may cross 5.4% by the year of 2025 3 . In Turkey, 7.4% of population suffer from diabetes and also it is estimated that the number of patients will be increased to 9.6% of population by the year of 2030 2 .…”
Section: Introductionmentioning
confidence: 99%